138 NICOTINAMIDE ADENINE DINUCLEOTIDE PHOSPHATE OXIDASE INHIBITION IMPROVES NEUROLOGIC FUNCTIONS IN SURGICALLY INDUCED BRAIN INJURY. Issue 1 (1st January 2007) - Lo, W.; Bravo, T.; Jadhav, V.; Titova, E.; Tang, J.; Zhang, J.
Abstract : Purpose: Neurosurgical procedures can result in brain injury by various means, including direct trauma, hemorrhage, retractor stretch, and electrocautery. This surgically induced brain injury (SBI) can cause postoperative complications such as brain edema following blood-brain barrier (BBB) disruption. In this study, we tested whether NADPH oxidase, an important reactive oxygen species (ROS)-producing enzyme, is involved in SBI using transgenic mice lacking gp91phox subunit of NADPH oxidase (gp91-KO) and apocynin, a specific inhibitor of NADPH oxidase. Methods: A mouse model of surgically induced brain injury (SBI) was used, which involves stereotaxic resection of a part of the right frontal lobe. gp91-KO and wild-type (WT, C57BL/6J) littermates were grouped into SBI and sham-surgery groups. Alternatively, mice were grouped into SBI and apocynin-treated (5 mg/kg, IP 30 minutess before surgery) groups. Neurologic function and brain edema (brain water content) were evaluated at 24-hour post-SBI. Oxidative stress indicated by lipid peroxidation (LPO) was measured at 3 and 24 hours post-SBI. Results: Brain edema was observed 24-hour post-SBI in both gp91-KO and wild-type group as compared with the sham group; however, there was no significant difference between the gp91-KO and wild-type groups. Brain edema was also not affected by apocynin pretreatment. LPO levels were significantly higher in SBI group in both gp91-KO and wild-type groups compared with the sham group. LPO levels were significantly attenuated at 3-hour post-SBI by apocynin pretreatment but not at 24-hour post-SBI. A trend, although without statistical significance, was noted toward attenuation of LPO in the gp91-KO animals as comp. The gp91-KO mice and apocynin-treated mice, however, showed significantly improved neurologic scores 24-hour post-SBI compared with the wild-type and vehicle-treated mice, respectively. Conclusions: Chronic and acute inhibition of NADPH oxidase activity does not affect brain edema; however, it improves neurologic functions after SBI. Further investigation is needed to find if other mechanisms, such as apoptosis or inflammation, are involved in improved neurologic functions after NADPH oxidase inhibition.